Efektifitas Kinerja Keuangan Zakat Bank Umum Syariah di Indonesia - Supami Wahyu Setiyowati (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
The performance evaluation of zakat institutions was previously limited to the Allocation To Collection Ratio (ACR). The development of measurement performance of zakat managers has now changed to assess the overall performance of the activities of zakat management institutions. In the assessment of the performance, there are five measurement ratios. This study aims to reveal the effectiveness of the performance of Islamic Commercial Banks in Indonesia in its efforts in the collection and distribution of zakat funds. This research uses a descriptive qualitative approach. It collects data on the source and uses zakat funds in 14 Sharia Commercial Bank Annual Reports for a period 2016 to 2018. The analytical tool used to measure financial performance is to use a 2 Ratio Analysis relevant to the conditions in Sharia Commercial Bank, i.e., Activity Ratio and Growth Ratio. The results showed that the Sharia Commercial Bank Zakat Fund Activity Ratio showed good performance but decreased performance yearly. Also, the ratio of Zakat Funds for Islamic Commercial Banks still has poor performance. If there is no significant improvement in the management of zakat funds, it could impact the reputation of the Sharia Commercial Bank in Indonesia.